2015
DOI: 10.1111/trf.13366
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative use of platelets in a 6‐year‐old with acute appendicitis and a myosin heavy chain 9–related disorder: a case report and review of literature

Abstract: This patient's PLT count was within guidelines to warrant transfusion; however, some patients with MYH9 mutations have counts above the transfusion threshold. To the authors' knowledge, there are no set guidelines for preoperative prophylaxis in a patient with an MYH9 deficiency. The management of the bleeding diathesis in these patients, especially in the setting of invasive procedures, is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…We also considered the validity of platelet transfusion in ES patients. Eichel et al reported that there were no guidelines for preoperative prophylaxis in patients with MYH9 mutations or the management of the bleeding tendency in these patients, especially in invasive procedures . However, our experiences suggest that keeping a platelet count above 100 × 10 9 /L during the perioperative period helped in the management of ES patients.…”
Section: Discussionmentioning
confidence: 74%
“…We also considered the validity of platelet transfusion in ES patients. Eichel et al reported that there were no guidelines for preoperative prophylaxis in patients with MYH9 mutations or the management of the bleeding tendency in these patients, especially in invasive procedures . However, our experiences suggest that keeping a platelet count above 100 × 10 9 /L during the perioperative period helped in the management of ES patients.…”
Section: Discussionmentioning
confidence: 74%